The 3D Tune-In Toolkit: A C++ library for binaural spatialisation, and hearing loss / hearing aid emulation - Reyes-Lecuona, Arcadio; Cuevas-Rodríguez, María; González-Toledo, Daniel; Garre, Carlos; De-la-Rubia-Cuestas, Ernesto Jesús; Molina-Tanco, Luis; Rodríguez-Rivero, Ángel; Picinali, Lorenzo (My University, 2019)
This contribution presents the 3D Tune-In (3DTI) Toolkit, an open source C++ library for binaural spatialisation which includes hearing loss and hearing aid emulators. Binaural spatialisation is performed through convolution with user-imported Head Related Transfer Functions (HRTFs) and Binaural Room Impulse Responses (BRIRs), including additional functionalities such as near- and far-field source simulation, customisation of Interaural Time Differences (ITDs), and Ambisonic-based binaural reverberation. Hearing loss is simulated through gammatone filters and multiband expanders/compressors, including advanced non-linear features such as frequency smearing and temporal distortion. A generalised hearing aid simulator is also included, with functionalities such as dynamic equalisation, calibration from user-inputted audiograms, and directional processing.
Keywords: Audífonos; Perdida de audición-Tratamiento; Sordera-Tratameinto